2018
DOI: 10.1093/jac/dky284
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbapenemase-producing Enterobacteriaceae from colonized patients in a university hospital in Madrid, Spain, during the R-GNOSIS project depicts increased clonal diversity over time with maintenance of high-risk clones

Abstract: We describe a polyclonal and changeable CPE population over time. Coexistence of worldwide disseminated clones, such as ST11-OXA-48- K. pneumoniae, with unrelated and emerging OXA-48-E. coli clones, depicts a disturbing CPE epidemiology in our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 19 publications
2
53
0
6
Order By: Relevance
“…During the study period, the incidence of CPE colonization in our institution was 2%, and it was due to mainly the success and persistence of OXA-48-producing K. pneumoniae clones, particularly the sequence type 11 (ST11) high-risk clone (34). Similar results have been reported in other Spanish hospitals (35)(36)(37).…”
Section: Discussionsupporting
confidence: 84%
“…During the study period, the incidence of CPE colonization in our institution was 2%, and it was due to mainly the success and persistence of OXA-48-producing K. pneumoniae clones, particularly the sequence type 11 (ST11) high-risk clone (34). Similar results have been reported in other Spanish hospitals (35)(36)(37).…”
Section: Discussionsupporting
confidence: 84%
“…The study enrolled all patients admitted to two medical wards (gastroenterology and pneumology) and two surgical wards (neurosurgery and urology) in the hospital. The full details of the R-GNOSIS study in our hospital, including the study population and CPE characterization, have been previously reported by Hernandez-Garcia et al 18,23 . Briefly, from March 2014 to March 2016, 28,089 rectal swabs were collected from 9,275 patients, and 171 pOXA-48-carrying enterobacteria strains were isolated and characterised from 105 patients (Figure 1, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…We studied samples collected from patients admitted in a Spanish university hospital from March 4th, 2014, to March 31 st , 2016, as part of an active surveillance-screening program for detecting ESBL/carbapenemase-carriers (R-GNOSIS-FP7-HEALTH-F3-2011-282512, www.r-gnosis.eu/) 18,22,23,36 . This study was approved by the Ramón y Cajal University Hospital Ethics Committee (Reference 251/13), which waived the need for informed consent from patients on the basis that the study was assessing ward-level effects and it was of minimal risk.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations